PERSAMAAN INFLOW PERFORMANCE RELATIONSHIP CURVE TIDAK BERDIMNEBSI UNTUK RESERVOIR BATUAN PASIR HETEROGEN DENGAN TENAGA PENDORONG GAS TERLARUT - Beckenbauer Yap, Romario
There are many researches have been conducted to find correlations IPR (Inflow Performance Relationship) in the solution gas drive sand stone reservoir. Numerical and analytical approaches have been carried out to find this relationship. But numerical methods and analytical approaches usually used to do with assumpsion that some reservoir properties are considered uniform. This assumption is actually very different from the actual reality that is often encountered in the field which, in fact, there is heterogeneity in rock properties, especially permeability and porosity that are very diverse and will affect the flow pattern and then will affect the correlation IPR (Inflow Performance Relationship) eventually. In this paper I will consider the variables that affect the heterogeneity of the reservoir properties that affecting IPR (Inflow Performance Relationship) and is limited to the effect of heterogenity of permeability and porosity with a heterogeneity variables like standard deviation. It will produce a new IPR that includes heterogeneity variable became observed parameter.